2015
DOI: 10.1001/jama.2015.6734
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Early Screening for Patent Ductus Arteriosus and In-Hospital Mortality Among Extremely Preterm Infants

Abstract: for the Hemodynamic EPIPAGE 2 Study Group IMPORTANCE There is currently no consensus for the screening and treatment of patent ductus arteriosus (PDA) in extremely preterm infants. Less pharmacological closure and more supportive management have been observed without evidence to support these changes.OBJECTIVE To evaluate the association between early screening echocardiography for PDA and in-hospital mortality. DESIGN, SETTING, AND PARTICIPANTSComparison of screened and not screened preterm infants enrolled i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
85
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 128 publications
(93 citation statements)
references
References 40 publications
(52 reference statements)
5
85
1
2
Order By: Relevance
“…This is presumably why extremely low values of cerebral oxygenation were not observed during the first 6 days after birth. The reasoning behind early treatment is underlined by a recent study by Rozé et al , who reported that early screening and treatment for a hsPDA was associated with lower in-hospital mortality and likelihood of pulmonary haemorrhage 37. In our study, infants with a non-sPDA show slightly lower cerebral oxygenation after 6 days and a sharper decline over time compared with infants with a closed duct.…”
Section: Discussionsupporting
confidence: 49%
“…This is presumably why extremely low values of cerebral oxygenation were not observed during the first 6 days after birth. The reasoning behind early treatment is underlined by a recent study by Rozé et al , who reported that early screening and treatment for a hsPDA was associated with lower in-hospital mortality and likelihood of pulmonary haemorrhage 37. In our study, infants with a non-sPDA show slightly lower cerebral oxygenation after 6 days and a sharper decline over time compared with infants with a closed duct.…”
Section: Discussionsupporting
confidence: 49%
“…The wide variability of bedside practices and our statistical results support the validity of our propensity score. Here, as for other clinical policies, such as PDA screening strategies,28 our analysis can provide results otherwise difficult to identify in randomised trials 29. Finally, this study is the first to our knowledge that has the ability to distinguish, among hypotensive infants who received antihypotensive treatments, those who had only isolated low BP values from those who had additional signs of haemodynamic compromise.…”
Section: Discussionmentioning
confidence: 88%
“…The significant PDA results in large volume ductal shunting,10 excessive pulmonary blood flow9 and haemorrhagic pulmonary oedema 11. Early PDA screening,12 early PDA therapy13 and indomethacin prophylaxis6 have all been found to reduce the incidence of pulmonary haemorrhage in very preterm infants but not overall survival. However, interpretation of clinical trials in this area has often been complicated by open-label rescue therapy available to the placebo groups 13 14…”
Section: Discussionmentioning
confidence: 99%